Synthesis and Evluation of Lignosulphonate Mannich Base as Eco-Friendly Corrosion Inhibitors - Zhang, Jie; Tian, Jing; Wang, Hai-Yang; Zhang, Li; Chen, Gang; Zhao, Jing-Rui; Li, Hong (Asian Journal of Chemistry, 2014)
According to the corrosion of oilfield acidification, this paper mainly used aliphatic amine, methanal and sodium lignosulphonate as the main raw materials to produce a new Mannich base as an eco-friendly corrosion inhibitor. The inhibition of mild steel corrosion in 5 % hydrochloric acid solution by Mannich bases was studied by weight loss technique. Through single factor experiments, determined the optimal mole ratio and the types of raw material are selected. Meanwhile, the influences of temperature and corrosion inhibitor dosage on the corrosion inhibiting performance of the products were studied. Their adsorptions on the surface of mild steel and inhibition mechanism were also discussed.